The Effect of Digitalization of Work Processes and Digital Skills Training on the Productivity of Employees of Manufacturing Companies - Ika Putri Aisya Ningrum; Mutiara Retno Lestari (DPPM Universitas Pelita Bangsa, 2024)
This study analyzes the impact of digitization of work processes and digital skills training on employee productivity in manufacturing companies in Cikarang. Digitalization is assessed based on operational transformation, while digital skills training is evaluated through the development of human resource competencies. The results show that digital skills training plays an important role in increasing employee productivity, more than just the adoption of new technologies. The research method uses a quantitative approach with questionnaires and SmartPLS-based data analysis. The results of the analysis revealed a significant relationship between digital skills training and increased productivity. Moderation factors such as organizational culture and technology adoption rates also have a relevant impact. The study emphasizes the importance of a digital transformation strategy integrated with employee training to meet the challenges of the fourth industrial revolution. Strategic recommendations are given to optimize technology implementation and competency development in the manufacturing sector.